EVALUATION OF IMMUNOBLOT RESULTS FOR DETERMINATION OF ANTIBODIES TO LYME DISEASE PATHOGENS IN CHILDREN OF TERNOPIL REGION - Nykytyuk, S. O.; Klymnyuk, S. I.; Klishch, I. M.; Levenets, S. S. (International Journal of Medicine and Medical Research, 2022)
Background. Lyme disease (LD) is a multisystem disorder caused by Borrelia burgdorferi and other similar tick-borne Borrelia. Objective. The aim of the research was to compare the results of the serological examination of children with different forms of Lyme disease. Methods. We observed the group of children (n=178) aged 1 to 14 years who were bitten by ticks. The control group consisted of 30 healthy children. Ticks were identified using a stereomicroscopic SEO system which included a stereomicroscope, a colour digital camera and a photoadapter. B. burgdorferi sensu lato (sl) (B. burgdorferi sensu stricto, B. afzeliі and B. garinii), B. miyamotoi, A. phagocytophilum DNA in blood were determined by real-time PCR. Baseline investigations related to clinical and immunological studies, including ELISA and Immunoblot, were performed. Results. The survey covered 178 child parents bitten by ticks. Borrelia burgdorferi sensu lato (B. afzelii, B. burgdorferi sensu stricto and B. garinii), B. miyamotoi and A. phagocytophilum were identified. Serological results in children with different forms of Lyme disease were compared. Conclusions. It is established that B. burgdorferi sensu lato; B. miyamotoi; and A. phagocytophilum are pathogens that cause erythema migrans in children. The presence of specific IgG (only positive results) to B. burgdorferi s.l. by immunoblot was confirmed in 83.8% of individuals who had positive and intermediate results in the ELISA test.